Dynamic scheduling with Microsoft Project 2013 : the book by and for professionals - Ambriz, Rodolfo; Landa, Mario, 1977-; Wilson, Keith (J. Ross Publishing, Inc. : International Institute for Learning, Inc., 2015)
Microsoft Project 2013 is a powerful software tool, and like all tools it requires knowledge and skill to be used to its maximum potential. This fully revised new edition provides users with everything they will need to more easily and effectively manage projects to a successful conclusion. Designed for the busy, practicing project manager, it will help you get up to speed quickly with the new and enhanced features of Project 2013 (including Project Pro for Office 365) and enable you to create effective schedules using best practices, tips & tricks, and step-by-step instruction. Through the use of helpful screenshots, hands-on exercises, illustrations, and review questions, this guide instructs you on how to build dynamic schedules that will allow you to explore what-if scenarios and dramatically decrease the time you spend making static schedule changes. It also provides validated training material for the new Microsoft Certification Exam 74-343. --